Design recommendations and sizing guidelines for small scale grid-connected decentralised energy systems - Panagiotou, Konstantina (2018)
Decentralised energy systems (DES) can be seen as a promising network topology which can potentially address the 21st century energy and power challenges that the existing hierarchical, centrally controlled power grid is required to face. Comprehensive design and representation of such systems are among the many obstacles which restrict the wider spread of DES. This thesis is concerned with the feasibility and profitability of small scale grid-connected DES located in UK. A suitable design and development procedure was proposed in this study for the analytical and detailed representation of the systems considered. The design procedure followed was integrated with the control, management and sizing strategies via the monitor of the system operation and the power flow. The effect of different technical parameters on the system performance and viability was investigated and the outcome was utilised in planning and scheduling decisions. Finally, comparisons between different specific test scenarios, energy systems, overnight charging control algorithms, energy storage sizes, etc. were implemented and conclusions regarding the system financials were drawn. This study can be seen as a design and sizing guide or a process simulation interactive software which provides design recommendations, sizing guidelines and useful system insights to the end users and the management authority/aggregators.